MATHEMATICAL MODELING OF THE VARIATION IN WATER QUALITY ALONG THE NETWORK OF WATER SUPPLY OF SATU MARE MUNICIPALITY, ROMANIA - DIPPONG, Thomas; MIHALI, Cristina; GOGA, Firuţa; ARDELEAN, Gheorghe (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Drinking water quality in the water network supply of the Satu Mare municipality was investigated, aiming to quantify the variation of some physico-chemical parameters with the distance from the water treatment plant. Usually, water quality decreases in the drinking water distribution systems due to unwanted physical, chemical and biochemical reactions occurring in the distribution systems. The variation of the main physicochemical parameters of drinking water such as turbidity, pH, oxidability, chlorides and free residual chlorine concentration, conductivity, iron content, water hardness and nitrates concentrations was studied. The drinking water samples were collected weekly during the year 2013 from 16 fixed points of the distribution network of Satu Mare. The statistical analysis of the results was accomplished and presented. Univariate and bivariate regression models of the water quality variation with the distance from the water treatment plant were proposed. The distance from the water treatment plant to the each sampling point was established by measuring the length of pipelines crossed by water until that sampling point. The sampling points were chosen on the main routes of water distribution pipes in the main districts of the city of Satu Mare. These mathematical models attempted to capture the variation of the physico-chemical parameters of drinking water along the water network supply. An increasing trend of turbidity, water conductivity, water hardness and nitrates content of water was observed while the free chlorine content showed a decreasing trend.